2011
DOI: 10.1021/jp2046239
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Signature of 2-[4-(Dimethylamino)styryl]-1-methylquinolinium Iodide: A Case of Negative Solvatochromism in Water

Abstract: Photophysics of the 2-[4-(dimethylamino) styryl]-1-methylquinolinium iodide (DASQMI) molecule has been studied in different solvents by steady-state and time-resolved emission spectroscopy and also with quantum chemical calculations. The probe molecule exhibits a strong solvent-polarity-dependent characteristic. The low-energy fluorescence band of DASQMI shows an anomalous 40 nm blue shift in water from that in dimethyl sulfoxide (DMSO); though in deuterium oxide the normal trend of red shift was observed. A m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 29 publications
0
14
1
Order By: Relevance
“…On going from the low‐polarity DCM to the highly polar water (W), the spectral blueshifts in the absorption band are 4240, 2130, and 3540 cm −1 for A , B , and C , respectively. An investigation of the absorption and fluorescence properties of B in a few solvents has been reported in a recent paper;28 the obtained results are quite different with respect to ours (results are oddly blueshifted with respect to those widely reported in the literature for R ) but because the NMR spectroscopy analysis of this compound leaves no doubt about its structure and the quantum mechanical calculations excellently reproduce the experimental spectra, we consider our data reliable. The important solvatochromism observed for the A – C compounds may be an indication of a certain charge‐transfer character of the S 0 –S 1 transition (further evidence is provided by QC calculations, see below), as also other experimental findings seem to indicate.…”
Section: Resultscontrasting
confidence: 86%
“…On going from the low‐polarity DCM to the highly polar water (W), the spectral blueshifts in the absorption band are 4240, 2130, and 3540 cm −1 for A , B , and C , respectively. An investigation of the absorption and fluorescence properties of B in a few solvents has been reported in a recent paper;28 the obtained results are quite different with respect to ours (results are oddly blueshifted with respect to those widely reported in the literature for R ) but because the NMR spectroscopy analysis of this compound leaves no doubt about its structure and the quantum mechanical calculations excellently reproduce the experimental spectra, we consider our data reliable. The important solvatochromism observed for the A – C compounds may be an indication of a certain charge‐transfer character of the S 0 –S 1 transition (further evidence is provided by QC calculations, see below), as also other experimental findings seem to indicate.…”
Section: Resultscontrasting
confidence: 86%
“…This observation reflects the higher electron‐acceptor ability of the ‐ + PPh 3 versus ‐PPh 2 O group. The values of λ abs for all the studied species 1 – 9 are only slightly dependent on the solvent polarity, as the solvation sphere remains virtually unrelaxed upon fast vertical excitation . Nevertheless, for all the salts, the lowest‐lying absorptions in water are systematically blue‐shifted with respect to DCM solutions (hypsochromic shifts of 90 cm −1 for 1 to 1183 cm −1 for 6 ); this can be termed as negative solvatochromism, as described for other ionic bipolar dyes…”
Section: Resultsmentioning
confidence: 76%
“…However, to date, there has been little investigation on the effect of changing the solvent used, which is a very simple environment change [ 19 ]. Previous studies have reported only shifts of the emission peaks when the solvent was changed [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%